EHO-85, Novel Amorphous Antioxidant Hydrogel, Containing Olea europaea Leaf Extract-Rheological Properties, and Superiority over a Standard Hydrogel in Accelerating Early Wound Healing: A Randomized Controlled Trial - José Verdú-Soriano; Marisol de Cristino-Espinar; Silvia Luna-Morales; Caridad Dios-Guerra; Antonio Casado-Díaz; José Manuel Quesada-Gómez; Gabriel Dorado; Miriam Berenguer-Pérez; Susana Vílchez; Jordi Esquena; Leocadio Rodríguez-Mañas; José Luis Lázaro-Martínez (MDPI AG, 2023)
Many advanced wound healing dressings exist, but there is little high-quality evidence to support them. To determine the performance of a novel amorphous hydrogel (EHO-85) in relation to its application, we compared its rheological properties with those of other standard hydrogels (SH), and we assessed the induction of acceleration of the early stages of wound healing as a secondary objective of a prospective, multicenter, randomized, observer-blinded, controlled trial. The patients were recruited if they had pressure, venous, or diabetic foot ulcers and were treated with EHO-85 (n = 103) or VariHesive® (SH) (n = 92), and their response was assessed by intention-to-treat as wound area reduction (WAR (%)) and healing rate (HR mm2/day) in the second and fourth weeks of treatment. Results: EHO-85 had the highest shear thinning and G'/G" ratio, the lowest viscous modulus, G", and relatively low cohesive energy; EHO-85 had a significantly superior effect over SH in WAR and HR, accelerating wound healing in the second and fourth weeks of application (p: 0.002). This superiority is likely based on its optimal moisturizing capacity and excellent pH-lowering and antioxidant properties. In addition, the distinct shear thinning of EHO-85 facilitates spreading by gentle hand pressure, making it easier to apply to wounds. These rheological properties contribute to its improved performance.